Scrutinizing the Awareness of Hidden Curriculum: Connecting Lecturers to Themselves, Students, and Non-Engineering Study Programs - Welly Ardiansyah; Risnawati; Zakaria; Lutfi Asyari; Abdurrahmansyah - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The hidden curriculum plays a crucial role in the entire teaching process, and there is no doubt about that. It possesses the irreplaceable value and function of explicit curriculum. Therefore, teaching at a college should pay attention to utilizing hidden curriculum. On the basis of fully understanding the characteristics and functions of the hidden curriculum, this study analyze the understanding of the hidden curriculum, interviewed selected lecturers to probe deeper regarding how they use the hidden curriculum and made observations notes on classroom environments and interactions. A mixed-method approach is used in this study. Purposive sampling was used to select 100 non-engineering lecturers in State Polytechnic of Sriwijaya for the statistical society. To collect information, survey, interview, and observation were applied. The findings showed that the majority of lecturers had knowledge of the hidden curriculum and utilized it to improve their classroom through body language, tone of voice, physical classroom changes, setting and maintaining expectations and norms, and reflecting upon their teaching. It was also found that all departments brought their mission statements and ethos to life.. A further contribution of the study is to provide a deeper understanding of the hidden curriculum enacted in private higher education, as well as what lecturers experience the hidden curriculum to be like. A better understanding of hidden curriculum is necessary to improve its use in higher education.